Audio-based approaches in tuning retrieval of gamelan ensemble - Hamdan, Sinin (2021)
Preliminary studies on gamelan instruments namely bonang, peking and kenong discussed in this work focus on their physical structure, tunings, and sound production. Since sound descriptions can only be measured by listening and are at the discretion of the creator, this work discusses about how to distinguish gamelan frequencies in a signal and the time-localized frequency content for each tone at a given time. This study focuses on the audio-based approach to tuning retrieval where the fundamental and overtone pitch is shown at all frequencies at a given time using Fourier transform, spectra, spectromorphology, and spectrograms. Three approaches used in retrieving tunings of gamelan are as follows: chladni patterns experiment using fine particle (sand), acoustic excitation from speaker for non-contact sinusoidal acoustic excitation and non-contact laser detector at specific eigen frequency, electronic speckle pattern interferometry (espi) for coherent addition of speckle fields diffracted by object and reference fields and laser doppler vibrometer (LDV) captured the vibration of the eigen frequency from the gong. Picoscope Melda analyser and Adobe using voltage-based triggers generate fast fourier transform (FFT) producing a spectrum, the decay signal is used for Q (loss factor) calculation. This study compares the harmonic, pitch, and size of bonang. The tone of peking was investigated using time-frequency analysis (TFA). Melda analyzer proved that all peking sustained the initial fundamental frequency and overtone at t=0 until 2s. This work also looks into timbral visualization of bonang. The bonang's sound profile has distinct characteristics, indicating a high recognition rate. The spectrogram revealed a simple fundamental frequency indicated by the brightest colours. The Q factor indicates the long-term viability or rapid decay. This research shows some of the preliminary findings and challenges associated with the analysis of the acoustic properties of selected gamelan instruments. When listening to its tones in a musical environment, individual harmonics of a complex tone and partial identification may be nearly impossible to discern by the human ear. The method of temporal localization on the dominant frequency at its unique time for each tone allows for the detection of frequencies present in the signal. According to this research, one gamelan's intonation, tone, and sentiments will always differ from another gamelan's. As a result, it proved that these primitive methods may provide tuning to the gamelan set. Field trips to the Jogjakarta gamelan builders reveal that the gamelan tuner solely tuned the gamelan based on hearing, which is passed down from generation to generation. The maker's intuition permits him to create a specific 'signature' through sound that is unique to a given gamelan set.